Herpes Simplex Viral Encephalitis Masquerading as a Classic Left MCA Stroke - Peter A. Abdelmalik; Timothy Ambrose; Rodney Bell (Case Reports in Neurological Medicine)
Objective. Stroke is a clinical diagnosis, with a history and physical examination significant for acute onset focal neurological symptoms and signs, often occurring in patients with known vascular risk factors and is frequently confirmed radiographically. Case Report. A 79-year-old right-handed woman, with a past medical history of hypertension, hyperlipidemia, and prior transient ischemic attack (TIA), presented with acute onset global aphasia and right hemiparesis, in the absence of fever or prodrome. This was initially diagnosed as a proximal left middle cerebral artery (MCA) stroke. However, CT perfusion failed to show evidence of reduced blood volume, and CT angiogram did not show evidence of a proximal vessel occlusion. Furthermore, MRI brain did not demonstrate any areas of restricted diffusion. EEG demonstrated left temporal periodic lateralized epileptiform discharges (PLEDs). The patient was empirically loaded with a bolus valproic acid and started on acyclovir, both intravenously. CSF examination demonstrated a pleocytosis and PCR confirmed the diagnosis of herpes simplex viral encephalitis (HSVE). Conclusions. HSVE classically presents in a nonspecific fashion with fever, headache, and altered mental status. However, acute focal neurological signs, mimicking stroke, are possible. A high degree of suspicion is required to institute appropriate therapy and decrease morbidity and mortality associated with HSVE.